Effectiveness of a Brief Mindfulness Based Intervention to Promote Posttraumatic Growth in Cancer Patients - Nurfadhilah Nurfadhilah; Widyastuti Widyastuti; Ahmad Ridfah (Humaniora, 2017)
The purpose of this study was to determine the effectiveness of a brief mindfulness based intervention to promote posttraumatic growth in cancer patients. The research design used was untreated control group design with pretest and posttest samples. Subjects in this study were 21 cancer patients that were divided into an experimental group (n = 10) and a control group (n = 11). Data were analyzed using Anova Mixed Design. The analysis showed significant changes of posttraumatic growth in the experimental group (MD=-14,400; p=0,000, p<0,05) and in the control group changes of posttraumatic growth were not significant (MD=-0,273, p=0,914, p>0,05). The results show that a brief mindfulness based intervention, which in this case is mindfulness training and yield significant results towards increased scores of posttraumatic growth in cancer patients. Hence, mindfulness based intervention can be used as one of psychotherapy to help individual psychologically growth.